Phylogenetic Analysis of Spike and Envelope Proteins for a Number of Bat Coronaviruses for Understanding the Hypothesis of Possible Origin for the Novel 2019- nCoV - Ibrahim Ali, Salar (Kurdistan Journal of Applied Research, 2020)
Coronavirus Disease 19 (COVID-19) emergence reveals globally a great health issue and due to the limited information and knowledge on the origin of this novel coronavirus 2019 (2019-nCoV). Therefore, this study aims to investigate the evolution and analysis of molecular epidemiology for both Spike and Envelope proteins of 20 available complete genome sequences of different bat coronaviruses including 2019-nCoV in order to find out which type of bat coronaviruses is more likely to be the origin of this new 2019-nCoV and also multiple amino acid sequences of Envelope protein for all bat coronaviruses were aligned for the purpose of finding the greater probability of novel 2019-nCoV original host among bat coronaviruses. Phylogenetic tree analysis for Spike protein revealed that all 2019-nCoV related coronaviruses isolated from these species of species are discovered in China and Hong Kong and the Middle East bat are less likely to contribute in spreading or to become the origin of 2019-nCoV and all coronaviruses that from Hong Kong and China are located into one clade next to the clade that contains 2019-nCoV coronaviruses which indicates that this group of coronaviruses are genetically different for 2019-nCoV; moreover, Hong Kong and USA bat coronaviruses does not contain the bat coronavirus from China and are located into one clade far from the clade that contains 2019-nCoV indicates that all coronaviruses are genetically very different from 2019-nCoV, and USA bat coronavirus may has no role in generating of 2019-nCoV. The phylogenetic trees analysis of Envelope protein showed that Envelope protein of different coronaviruses are more similar in comparison to Spike protein, USA bat coronavirus has a relatively closeness relationship to 2019-nCoV. Furthermore, Envelope protein alignment showed the closely related amino acid sequence which confirms that the outcomes of phylogenetic tree analysis in which that these bat coronaviruses have genetically close relationship together and more interestingly amino acid sequence (MG772934.1) shows 100% identity with the amino acid sequence of 2019-nCoV (NC 045512.2) and the same virus has a close relationship in both Spike and Envelope due to that in both phylogenetic tree analysis are neighbored with 2019-nCoV in the same clade.